Nilai agama Islam dalam kesedaran beragama kalangan masyarakat Bajau Darat Kampung Penimbawan Tuaran, Sabah - Qurratu Ain Rapihi; Zaizul Ab Rahman (Pusat Kesejahteraan Insan dan Komuniti, Universiti Kebangsaan Malaysia, 2018)
Generally, the Bajau divided into two Sea Bajau living in the eastern part of Sabah Bajau Darat also known as just stay in the western part of Sabah. This difference is based on their geographical placement of the state. Dialect speech Bajau Bajau sea and land is also different. Their main activity is farming, breeding and fishing. In terms of religion, values awareness in society of the Muslim Bajau have preceded other indigenous tribes in the interior of Sabah, who was yet to embrace. However, awareness values of the Islamic religion in practice among the Bajau community is different and vary. This paper aims to identify the values of religion in religious awareness among the Bajau Sabah at Kampung Penimbawan Tuaran Sabah and their role as agents of the spread of Islam in the state. The design of this paper uses descriptive and regration quantitative method based on analysis of the findings of previous studies related to land in Sabah Bajau community. The results showed that the values of Islam in the religious consciousness Bajau Darat and their role as agents of the spread of Islam is still at a low level which shown the value of religion among regration ibadah and akhlak are R= 0.686 . The conclusion of the descriptive also showed that the frequency of ibadah at the range of moderate with 79% and the frequency of akhlak which both are the values of religious of Bajau at Kampung Penimbawan is low with cumulative percent 88.6%.